2022
DOI: 10.1029/2021je007177
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of APXS‐Derived Chemistry of the Clay‐Bearing Glen Torridon Region and Mount Sharp Group, Gale Crater, Mars

Abstract: The Glen Torridon stratigraphic sequence marks the transition from the low energy lacustrine-dominated Murray formation (Mf) (Jura member: Jm) to the more diverse Carolyn Shoemaker formation (CSf) (Knockfarril Hill member: Knockfarril Hill; Glasgow member: Glasgow). This transition defines a change in depositional setting. Alpha Particle X-ray Spectrometer (APXS) results and statistical analysis reveal that the bulk primary geochemistry of Mf targets are broadly in family with CSf targets, but with subtle comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 70 publications
(152 reference statements)
3
35
0
Order By: Relevance
“…Geochemical analyses indicated that the GT region is compositionally similar to Murray formation rocks encountered earlier in the mission but with elevated abundances of crystalline phyllosilicates and minor changes in volatile chemistry indicative of a complex geologic history. Data from the Alpha Particle X-ray Spectrometer (APXS) showed that the GT region is geochemically similar to median Murray formation composition (Berger et al, 2020;O'Connell-Cooper et al, 2022). The Chemistry and Mineralogy (CheMin) X-ray Diffractometer (XRD) detected elevated abundances of phyllosilicates in the GT region, consistent with the orbital data, and lower amounts of hematite compared to the VRR (Thorpe et al, 2022).…”
mentioning
confidence: 63%
“…Geochemical analyses indicated that the GT region is compositionally similar to Murray formation rocks encountered earlier in the mission but with elevated abundances of crystalline phyllosilicates and minor changes in volatile chemistry indicative of a complex geologic history. Data from the Alpha Particle X-ray Spectrometer (APXS) showed that the GT region is geochemically similar to median Murray formation composition (Berger et al, 2020;O'Connell-Cooper et al, 2022). The Chemistry and Mineralogy (CheMin) X-ray Diffractometer (XRD) detected elevated abundances of phyllosilicates in the GT region, consistent with the orbital data, and lower amounts of hematite compared to the VRR (Thorpe et al, 2022).…”
mentioning
confidence: 63%
“…Bedding in this location is less than about 10 cm thick and consists of stacked toesets of tabular-tangential cross-stratification. The top of this unit was drilled (Glen Etive) and studied extensively for (Dehouck et al, 2022;O'Connell-Cooper et al, 2022) and potential preserved organics (McAdam et al, 2022). While grain-size is difficult to determine through this interval, high-resolution MAHLI mosaics taken from centimeters from the outcrop surface, along with ChemCam RMI image mosaics, locally show dimpled outcrop textures suggestive of fine-to-medium sand.…”
Section: Knockfarril Hill Membermentioning
confidence: 99%
“…The GT region shows a geochemical composition of the major elements that is broadly in line with the underlying Murray formation, but with some notable variability (e.g., Dehouck et al, 2021, this volume). In the Jura member, two endmembers have been identified from both the APXS and ChemCam measurements (e.g., Dehouck et al, 2021Dehouck et al, , 2022O'Connell-Cooper et al, 2022). These two endmembers were referred to as "rubbly" and "coherent" from the relative resistance to erosion of the corresponding rocks (Dehouck et al, 2022), with the "rubbly" consistently outcropping as small pieces of fragmented bedrock (e.g., Fig.…”
Section: Relation Between the Studied Facies And Regional Geochemical...mentioning
confidence: 99%
“…These two endmembers are mainly discriminated based on their MgO and K2O contents (Dehouck et al, 2021(Dehouck et al, , 2022O'Connell-Cooper et al, 2022). The "rubbly" endmember shows a K2O-rich (> 1.5 wt.%) and MgO-poor (usually <6 wt.%) composition, defined as the regional Type 2 composition by Dehouck et al, (2022).…”
Section: Relation Between the Studied Facies And Regional Geochemical...mentioning
confidence: 99%